(untitled) (Sebha University Conference Proceedings, 2024)
This study was conducted at the Food and Drug Control Center, Al-Falah Branch / Tripoli, to investigate the presence in milk of residual antibiotics commonly used in local dairy farms. The study took a period from May to August (2021). in which a hundred fresh cow’s milk samples were randomly collected from five different regions Libya (Al-Zawiya - Ghout Al-Rumman - Al-Najilah - Tajoura - Al-Sawani) at the rate of twenty samples per region. Knowing that the cows were fed concentrate (cow concentrate) and the prevailing natural pastures in their regions. The high-performance liquid chromatography device examined the milk samples with a UV detector and an isocratic method. The samples were subjected to solid phase extraction before analysis and a mobile phase consisting of methanol, acetonitrile, oxalic acid 0.01 mol/L (5%, 18%, 77%), with a flow rate of (0.7 ml/min). The results of the study were analyzed based on the statistical package program for social sciences (SPSS Statistics 20) and using the percentage (the number of samples containing antibiotic residue was calculated against the total number of samples examined as a percentage), and the Student t-test (T) to compare the averages for positive samples and the permissible limit for tetracycline internationally. The results showed that 4 (4%) out of 100 milk samples contained residues of the antibiotic (chlortetracycline), with an average total concentration of 68.85 ± 9.8 µg/L. 2 (50%) positive were samples from Al-Zawiya area and 2 (50%) positive were samples from Ghut Al-Rumman area